Performance analysis of software defined network using intent monitor and reroute method on ONOS controller - Putri Monika; Ridha Muldina Negara; Danu Dwi Sanjoyo (Bulletin of Electrical Engineering and Informatics, 2020)
Software defined network (SDN) provides high service flexibility to optimize network configuration based on network traffic. Traffic management able to solve traffic density in SDN. However, it will misuse the network bandwidth and links. One variant of the SDN controller, namely open network operating system (ONOS), provides an intent monitor and reroute (IMR) method that can optimize traffic management based on the description of an object in the ONOS application. This method can optimize the network bandwidth and links of SDN. The IMR can monitor the network and reconfigure the network to restore network connectivity by maximizing the use of each link when transmitting data. This study examines the impact of using IMR with a custom topology on ONOS to find the best scenario by performing traffic management on a data plane consisting of switches totaling 8-12 switches. The parameters measured in this study are bandwidth usage and quality of service (QoS). The results obtained in this study are IMR able to optimize the use of each link and maximize bandwidth usage in a network when distributing data and following TIPHON standards.